UV/Fe(II) synergistically activated S(IV) per-treatment on HA-enhanced Ca²⁺ scaling in NF filtration: fouling mitigation, mechanisms and correlation analysis of membrane resistance in different filtration stage - Liu, Wenkai (2022)
The aim of this study was to investigate the feasibility and fouling mitigation mechanisms of UV/Fe(II) synergistically activated sulfite (S(IV)) (UFS) pretreatment to alleviate membrane fouling caused by HA-enhanced Ca2+ scaling. After UFS treatment, hydrophobic substances and carboxyl groups structure were destroyed by the in-situ-generated SO•-4, resulted in a significant reduction of hydrophobic substances ratio and carboxyl group concentration. Due to the formation of more electropositive in-situ-generated Fe(III), the complexation between Ca2+ and carboxyl groups was weakened so that the bulk crystallization size on the membrane surface was greatly reduced. The filter cake enhanced osmotic pressure effect (CEOP) and concentration polarization effect were hence alleviated, as well as the surface roughness. At the microcosmic perspective, as the energy barrier between the membrane and foulants was increased significantly after pretreatment, the anti-foulants adsorption ability of the membrane was enhanced. Correlation analysis showed that the carboxyl concentration and density, HPO ratio, larger particle size (>100 nm) ratio, the Ca2+ concentration in the scaling layer and energy barrier all had a good correlation with the membrane resistance. This research not only provides an advanced oxidation technology that can effectively alleviate the synergistically-fouling effect of HA and Ca2+ of nanofiltration process, but also proposes a guidance for the UV/Fe(II) synergistically activated sulfite.